2014
DOI: 10.1265/jjh.69.24
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Effects of Hand Massage in Geriatric Facility Residents

Abstract: These results confirmed the benefits of complementary and alternative medicine including touching and massage found in previous studies. Hand massage prompted relaxation in geriatric facility residents in this experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Shimizu et al [45] did not observe significant variations in sCgA when assessing the effects of movement music intervention in female older adults. And, similarly, no effect of hand massage prompted relaxation was obtained in sCgA from female geriatric facility residents [46]. No indication was given in these mentioned studies on dementia status of participants.…”
Section: Discussionmentioning
confidence: 90%
“…Shimizu et al [45] did not observe significant variations in sCgA when assessing the effects of movement music intervention in female older adults. And, similarly, no effect of hand massage prompted relaxation was obtained in sCgA from female geriatric facility residents [46]. No indication was given in these mentioned studies on dementia status of participants.…”
Section: Discussionmentioning
confidence: 90%
“…16 Previous studies support an association of hand massage with improved comfort level of nursing home residents 17 and geriatric patients. 32,33 In addition, many studies have shown the effectiveness of back, feet, and hand massages on increasing patient comfort. 34,35 Hand massage may provide more effective comfort when combined with other therapies during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%